Combined Immunodeficiency Evolving into Predominant CD4+ Lymphopenia Caused by Somatic Chimerism in JAK3 - Ban, Sol A. (J Clin Immunol, 2014)
PURPOSE: Idiopathic CD4 lymphopenia constitutes a heterogeneous group of immunodeficiencies with characteristically low CD4+ T-cell counts with largely unknown genetic etiology. We here sought to determine the underlying molecular cause in an index family with two patients suffering from combined immunodeficiency that evolved into predominant CD4+ lymphopenia. The more severely affected index patient also presented with selective antibody deficiency against bacterial polysaccharide antigens. METHODS: For the genetic analysis, we used combined homozygosity mapping and exome sequencing. Functional assays included immunoblot analysis, flow cytometry and TCR Vβ spectratyping. RESULTS: A novel homozygous missense mutation was revealed in the kinase domain of JAK3 (c.T3196C, p.Cys1066Arg). Further analysis showed revertant chimerism in CD8+ T-cells in both patients. The additional presence of revertant CD4+ T-cells was associated with a milder clinical and immunological phenotype in the second patient, although the role somatic chimerism plays in amelioration of disease phenotype is uncertain, as presence of revertant cells had no effect on residual CD4 cell JAK3 signaling function. Residual activity of JAK3-dependent STAT3 and STAT5 signaling was also found in immortalized B-cell lines indicating a hypomorphic nature of the described mutation which likely contributes to the milder clinical phenotype. CONCLUSIONS: We here present the first case of revertant mosaicism in JAK3 deficiency, manifesting as combined immunodeficiency evolving into predominant CD4+ lymphopenia. Revertant chimerism or hypomorphic mutations in genes typically associated with more severe T-cell deficiency should be considered when assessing patients with milder forms of combined immunodeficiencies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10875-014-0088-2) contains supplementary material, which is available to authorized users.